The effects of ziprasidone on steady-state lithium levels and renal clearance of lithium - Apseloff, G (Blackwell Science Inc, 2000)
AIMS: To assess the potential of ziprasidone to alter the renal clearance and steady-state serum levels of lithium. METHODS: Healthy subjects who had stable serum lithium levels during the first 7 days of treatment with lithium 900 mg day(−1), given as two divided daily doses, were randomized to receive concomitant treatment with either ziprasidone, 40 mg day(−1), given as two divided daily doses, on days 9–11 followed by 80 mg day(−1), given as two divided daily doses on days 12–15 (n = 12), or placebo twice daily (n = 13). Ziprasidone or placebo was administered 2 h before each dose of lithium. RESULTS: Ziprasidone administration was associated with a 0.07 mmol l(−1) (13%) mean increase in steady-state serum lithium levels compared with a mean increase of 0.06 mmol l(−1) (10%) with placebo. Mean renal clearance of lithium decreased by 0.09 l h(−1) (5%) in the ziprasidone group and by 0.14 l h(−1) (9%) in the placebo group. None of these differences between the two groups was statistically or clinically significant. CONCLUSIONS: Ziprasidone does not alter steady-state serum lithium concentrations or renal clearance of lithium.